Analisis Kinerja Keuangan Pada Rumah Sakit Islam Arafah Jambi (Studi Empiris Pada Rumah Sakit Islam Arafah Jambi Periode 2018-2022) - sukarda, sukarda; Wahyudi, Ilham; Wijaya Z, Rico (Jurnal Akuntansi & Keuangan Unja, 2024)
The purpose of this research is to analyze and evaluate the implementation of the existing financial performance analysis at the Arafah Islamic Hospital, Jambi. The research method used by researchers is a qualitative descriptive method in which the method is carried out by collecting data related to financial statements such as: balance sheets, income statements and equity. The research also conducted interviews, observations, and documentation with the directors and hospital management as well as conducting analysis. The results of the research conducted by the researcher can then be concluded that: The Financial Performance Analysis at Arafah Islamic Hospital Jambi is good, because of the 8 indicators that the researchers did there were 6 that were good or 85% good enough including Current Ratio, Debt Collection Period, Turnover Fixed Assets, Return on Fixed Assets (ROA), Return on Equity (ROE), and Inventory Turnover Ratio. However, the ratio of subsidy claims and cash equivalents is not good or 15%.